ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK MENGGUNAKAN ALGORITMA NAIVE BAYES - Suwandi, Ahmad; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2023)
Current technological developments have brought changes to human lifestyles, such as lifestyle, selection of antic goods and communication equipment such as smartphones and other devices. Nowadays it is known that the collection of branded items is also a lifestyle trend such as bags, rings, clothes and other fashions. Batam as an industrial city encourages investors to invest in Batam, because Batam is the most strategic city and is an international trade route directly adjacent to Singapore. The problem that often occurs at PT Tas Import Sukses in serving consumers is that the goods sent are not on demand, so consumers suspect that the products traded do not have good quality. And if there is a problem, the company responds with a very slow time. The purpose of this study is to analyze consumer satisfaction with the quality of products at PT Tas Import Sukses using the Naïve Bayes method, to determine the level of consumer satisfaction with the quality of bag products. And the last is to find out the level of accuracy in determining product satisfaction and quality with the Naïve Bayes method. While the results of this study are that satisfaction is strongly influenced by the level of service, while the second order is product quality, where the average level of satisfaction accuracy using the naïve bayes algorithm is 91%, pression 89% and recall 88.33%.